Anti-human influenza protector antibody detected in horses as a zoonotic viruses - Mancini, Dalva Assunção Portari; Mendonça, Rita Maria Zucatelli; Pinto, José Ricardo; Mori, Enio; Fernandes, Wilson Roberto (Brazilian Journal of Veterinary Research and Animal Science, 2004)
This study aimed to investigate the incidence of the influenza virus, and its interspecies transmission cycle among horses. A comparative serological survey was performed using horse sera following challenge with both specific (equine) and non-specific (human) influenza virus strains. Bleedings of the 22 horses were performed during the years 1999 and 2000. Following treatment with kaolin (20%), added in rooster erythrocytes suspension (50%), for removal of non-specific antibodies, sera were titered against both Human and Equine Influenza virus, by the Hemagglutination Inhibition Assay(HI), recommended by WHO. The HI results of horse serological responses demonstrate cross reaction between both the specific strain, A/Eq1 (H7N7) ( 62.75%) and A/Eq2 (H3N8) (60.65%), and the non- specific strains, type A (H1N1) (79.5%) and A (H3N2) (94.45%) and type B (77.75%). It was noteworthy the high percentage of protection responses in equine sera aginst the non-specific strains, as compared with the specific strains. This finding suggests direct interspecies transmission of influenza virus as zoonotic viruses, particulary for the type B strain which is considered restricted to humans. It was the first report, in Brazil. Further studies are required to achieve a complete understanding of the incidence of influenza in our environment.